Workshop on Models for Copyright Education in Information Literacy: An Initiative of the International Federation of Library Associations and Institutions - Hinchliffe, Lisa Janicke (Journal of Copyright in Education & Librarianship, 2019)
The Workshop was organized the IFLA Information Literacy Section and the IFLA Copyright and Other Legal Matters Advisory Committee to provide a forum for discussing models for education on copyright, licensing, and related legal matters within the framework of library information literacy programs. With more than 14 countries represented, the papers and discussions were far-ranging and comprehensive, touching on issues of pedagogy, instructional design, learning theory, author rights, copyright limitations and exceptions, applications of the law nationally, international copyright, open access, and education for library and information science practitioners. The papers in this special issue started as presentations at the workshop but were further developed based on feedback and then through peer review before publication.